Understanding the local state, service delivery and protests in post-apartheid South Africa: the case of Duncan Village and Buffalo City Metropolitan Municipality, East London - Ndhlovu, Patricia (My University, 2016)
This research report rests on the argument that community protests are a reflection of different understandings of a decent life by protesters and state representatives. South Africa’s democracy has been characterised by continuities in community protests, mainly targeted at the state or its representatives. Interestingly, most scholarship is biased towards interpreting these protests from a community perspective with limited attention to the state-centred perspective. This ethnographic study explores subjectivities constructed around community protests by Duncan Village and the Buffalo City Metropolitan Municipality in East London. It employed participant observation, in-depth interviews and focus groups to collect data from state representatives, community members and protesters. The study shows how meanings of a decent life are constructed by different actors, and how these meanings inform the state’s approach to service delivery. It further explores the understanding of protest action from the perspective of state representatives and the protesters. It concludes that contestations over the scarce resources have led to the forging of and contestations over new identities like inzalelwane (born and bred) and abantu bokufika (newcomers) as these identities inform how state resources are allocated in Duncan Village. Furthermore, the installation of prepaid electricity metres, which is part of a project to electrify shacks, has exacerbated poverty in Duncan Village. Residents have resorted to protests to challenge what they consider to be threats to decent life. Through their experiences with the BCMM, protesting communities have come to realise that the state prioritises business interests at the expense of the interests of the marginalised masses. This has led to protesters assigning new meanings and significance to the old repertoires of protest. For the residents of Duncan Village, as long as the perceived promises of a decent life remain unrealised, the state and/or its representatives (BCMM) will continue to experience protests in the unforeseeable future.
A research report submitted to the Faculty of Humanities, University of Witwatersrand in partial fulfillment of the requirements for the degree of Master of Arts in Industrial Sociology Johannesburg 2015